The mechanism of action of particulate vaccine adjuvants - Sharp, Fiona A. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2010)
Particulate vaccine adjuvants (PVA) have been used in vaccines both experimentally and clinically for almost a century. However, the mechanisms by which adjuvants, such as alum and poly lactide-co-glycolide (PLG) microparticles promote immune responses are not well understood. This project set out to investigate the mechanisms by which PVA promote immune responses and the relationship between specific PVA characteristics and the induction of innate and adaptive immunity. Firstly, the ability of PVA to activate immune cells in vitro was investigated. These studies revealed that neither alum, PLG nor polystyrene (PS) microparticles promoted the maturation of dendritic cells (DC). Furthermore, the particulates did not directly promote cytokine production by DC. In contrast, PVA synergised with TLR agonists to dramatically enhance the secretion of IL-1β, IL-18 and IL-1α. The enhancement in IL-1β secretion was dependent on particle uptake and potassium efflux. Furthermore, the increase in IL-1β secretion was dependent on caspase-1 activation via the NLRP3 inflammasome.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.